COMMUNITY RESILIENCE THROUGH THE CAPACITY BUILDING SUSTAINABLE VILLAGE (WASTE MANAGEMENT ECOVILLAGE BASED IN THE VILLAGE OF KEJAGAN, TROWULAN, MOJOKERTO) - Hajar Nurma Wachidah; Ahmad Fageh; Pipit Sari Puspitorini; Erna Tri Asmorowati; Taswirul Afkar; Engkin Suwandana (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2022)
In order to achieve the sustainable development goals (SDGS), countries are expected to reduce waste and waste production through efforts known as 3r recycling, and reuse to ensure sustainable production and consumption patterns. This is one of the efforts to increase community inequality through economic sectors in the management of the rural governments of Kejagan, Trowulan,Mojokerto. This service to society begins with two problems: (1) Community outreach to increased service, increased public tranquility, improvements in service facilities in all areas including social, cultural, economic, security, health, education, law, and other comprehensive issues in the endemi era. (2) Partner have yet to understand how garbage management becomes economic goods and has high sales value in the endemic era as an improvement in local communities' resilience. The method of community service is community intervention and three main characteristics: community based local resource based and sustainable.